Shopping Behavior Webrooming in Fulfilling Individual Needs From A Perspective Self-Determination Theory - Rahma, Resita Septia; Ramdan, Abdi; Mawar Firdausi, Asri Sekar; Alim, Taqdirul (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
The development of current consumer behavior shows shopping behavior using more than one channel to reduce fog. This study tries to offer a theoretical concept of omnichannel shopping behavior based on self-determination theory to explain what drives and motivates consumers to do webrooming behavior. This study was conducted using a survey method on 206 consumers who had done webrooming behavior using SEM-PLS analysis. Empirical results indicate that the needs of the three individuals with self-determination are proven to be drivers of consumers in doing webrooming behavior. However, unlike the testing of moderation variables, the three self-determination needs do not fully moderate and only product characteristics moderate the relationship between autonomy variables and webrooming behavior